Women and literature in an essay by Montserrat Roig. - Silva Oliveira, Katia Aparecida da [UNESP] (Univ Estadual Paulista-unesp, 2015)
The questioning about the representation of woman in literature and about literature written by women is present in Montserrat Roig's literary composition. In her essay book Dime que me quieres aunque sea mentira (1991), besides texts focused on the act of writing, on the process of writing, on the representation of memory and also on the representation of Catalan culture and identity, there are two essays presented separately under the title of La mirada tuerta which deal with woman particularly as literary representation and with the position of women writers in literature. This work analyzes one of these essays: El Uno y la otra which is divided into three parts dealing, first, with the representation of woman. Then, it exams one vision about feminism and women as writers and, finally, it makes some remarks about the current scenery related to feminine writing in literature. The purpose here is the analysis of the essay, considering the way the text sets itself both in relation to woman in literature and in relation to alterity and feminist criticism which was well developed in the 20th century by writers such as Simone de Beauvoir, Kate Millet and Elaine Showalter among others.
Keywords: Woman; Feminine authorship; Feminism; Montserrat Roig